2019
DOI: 10.1155/2019/5796074
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Complete Remission of Hepatocellular Carcinoma: A Significant Predictor for Recurrence-Free Survival after Liver Transplantation

Abstract: Background Liver transplantation (LT) is a curative treatment for hepatocellular carcinoma (HCC) and the underlying primary liver disease; however, tumor recurrence is still a major issue. Therefore, the aim of this study was to assess predictors and risk factors for HCC recurrence after LT in patients within and outside the Milan criteria with a special focus on the impact of different bridging strategies. Methods All patients who underwent LT for HCC between 07/2002 and 09/2016 at the University Hospital of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Of note, young-onset HCC resulted in similar postoperative recurrence rate but presented a robust reduction in time to recurrence. The median time to recurrence ranges from 12.5 to 23 months based on previous reports (11,30). In the present study, 72.4% of HCC patients experienced recurrence, with a median recurrence−free survival of only 5.9 months (178 days).…”
Section: Discussionsupporting
confidence: 59%
“…Of note, young-onset HCC resulted in similar postoperative recurrence rate but presented a robust reduction in time to recurrence. The median time to recurrence ranges from 12.5 to 23 months based on previous reports (11,30). In the present study, 72.4% of HCC patients experienced recurrence, with a median recurrence−free survival of only 5.9 months (178 days).…”
Section: Discussionsupporting
confidence: 59%
“…26 Surveillance for HCC is particularly germane as the incidence of recurrence can be high as 20%-40% in the first year following treatment. 27,28 The NCCN guidelines recommend follow-up imaging after resection, transplantation, or locoregional therapy with CT or MRI scans every 3 to 6 months for 2 years, and every 6 to 12 months thereafter. 8 While posttreatment surveillance may provide a benefit among patients with colorectal, breast, and prostate cancer, [10][11][12]21 the use of "intense" surveillance in the postoperative setting remains a controversial topic.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that results of the therapy may be used to select LTx candidates more effectively. A positive response to treatment enables eligibility and decreases recurrence risk [ 16 , 30 , 51 53 ].…”
Section: Risk Factors Before Proceduresmentioning
confidence: 99%
“…In the present study, we discuss risk factors influencing the frequency of recurrence, including both those that may be assessed before and after transplantation. These include factors to help determine transplantation eligibility among patients that have the lowest recurrence risk, as well as classification and duration of follow-up of liver recipients to aid in the early diagnosis of possible recurrence, which may allow for more prompt and effective treatment ( Table 1 ) [ 7 , 19 , 20 , 27 30 ].…”
Section: Introductionmentioning
confidence: 99%